2020
DOI: 10.1590/1413-7054202044031019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of physiological analysis parameters associated with coffee beverage quality

Abstract: ABSTRACT The demand for high-quality coffee among consumers has generated a great deal of interest among producers in serving this market. Parameters for physiological analyses that can be associated with aspects of sensory analyses of coffee can ensure more reliable results for coffee quality assessments. The aim of this study was to investigate the potential of physiological analyses in determining coffee quality through multivariate analysis. Several samples from coffee bean/seed lots were placed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…MCA allows for the identification of similarities or distinctions in the sensory profiles. In order to observe the grouping of the samples based on the results obtained, a dendrogram was created based on the average of the results of the sensory analyses (Freitas et al, 2020; Rodríguez et al, 2021), using Hierarchical Cluster Analysis was performed using the average Euclidean distance and the Ward's method (Ward, 1963), and the number of clusters in the dendrogram was determined using Mojena's method (Mojena, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…MCA allows for the identification of similarities or distinctions in the sensory profiles. In order to observe the grouping of the samples based on the results obtained, a dendrogram was created based on the average of the results of the sensory analyses (Freitas et al, 2020; Rodríguez et al, 2021), using Hierarchical Cluster Analysis was performed using the average Euclidean distance and the Ward's method (Ward, 1963), and the number of clusters in the dendrogram was determined using Mojena's method (Mojena, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…The result showed that the total titratable acidity had a high relation with the quality of the beverage, but it had no relation with the perceptible acidity evatuated in the sensory analyses. According to Freitas et al (2020), this may be explained by the titrable acidity being related to occurrence of undesirable fermentation in the coffee due to the presence of fatty acids. In opossition, the perceptible acidity is associated to desirable acidity, suggesting the presence of acids that favor beverage flavor, such as citric, malic, and chlorogenic acids (Ramos et al, 2016;Sunarharum et al, 2014).…”
Section: Titratable Acidity Ph and Total Dissolved Solidsmentioning
confidence: 99%
“…However, information covering the potential related to the sensorial and physical quality of the Arabica coffee cultivars that has been recommended in Brazil is poor. Adding, these new recommended cultivars need more reserch aiming to evaluate and characterize these factors, particularlly in the state of Espírito Santo where coffee has grown in different soil and climate conditions in to geographic indication regions (Freitas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%